2012
DOI: 10.1117/1.jbo.17.9.098001
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectra of blood and urine for cervical cancer detection

Abstract: In the current study, the fluorescence emission spectra (FES) and Stokes shift spectra (SSS) of blood and urine samples of cervical cancer patients were obtained and compared to those of normal controls. Both spectra showed that the relative intensity of biomolecules such as porphyrin, collagen, Nicotinamide adenine dinucleotide, and flavin were quite out of proportion in cervical cancer patients. The biochemical mechanism for the elevation of these fluorophores is not yet definitive; nevertheless, these biomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 26 publications
3
32
0
2
Order By: Relevance
“…Masilamani et al found that the ratio of I 630 nm /I 585 nm in blood or urine samples was about one for normal controls and 2-3 for advanced cervical cancer patients [51]. Similar findings were also reported in blood samples of gastric cancer and breast cancer patients [40].…”
Section: Discussionsupporting
confidence: 70%
“…Masilamani et al found that the ratio of I 630 nm /I 585 nm in blood or urine samples was about one for normal controls and 2-3 for advanced cervical cancer patients [51]. Similar findings were also reported in blood samples of gastric cancer and breast cancer patients [40].…”
Section: Discussionsupporting
confidence: 70%
“…So the porphyrin concentration is more in the diseased blood components. [8][9][10] The porphyrin which gets accumulated abnormally on the tumor tissue experiences different local environment, such as aggregation, higher acidity and also bonding to the intercellular matrix. All these could lead to enhanced lifetime, 14,15 in tissue as shown by others and in blood, as shown in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…As the steady-state fluorescence spectra for blood samples of cancer patients have been studied extensively, [8][9][10][11][12] the discussion will focus only on one pertinent observation. In the field of fluorescence spectroscopy, the relative intensities of different peaks are more important than the actual, absolute intensities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Earlier, in a series of papers, we had shown the efficacy of spectral technique for diagnosis of different types of cancers. 6 As a logical extension, we demonstrate here the potential of spectral differentiation between IDA and β Thal patients. This method could prove useful to identify and separate IDA samples from those of Thal.…”
mentioning
confidence: 99%